2015
DOI: 10.3109/09286586.2015.1040924
|View full text |Cite
|
Sign up to set email alerts
|

Task Shifting for Eye Care in Eastern Africa: General Nurses as Trichiasis Surgeons in Kenya, Malawi, and Tanzania

Abstract: Attrition of general nurses trained in trichiasis surgery was high. Surgical productivity of trichiasis surgeons remained too low. It is likely that other approaches are needed to address the burden of trichiasis in the three countries. In terms of recommendations, training of trichiasis surgeons should be done in a "package," including a plan for provision of surgical equipment, continuous support and supervision, and outreach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…Rajak et al [ 32 ] found that nearly a quarter (24.7%) of those having received lamellar tarsal rotation suffered recurrence. Researchers note though that recurrence rates tend to be higher in those nurse-surgeons who performed the procedure only infrequently, an argument for frequent in-service training and practice [ 33 ].…”
Section: Tertiary Prevention Activitiesmentioning
confidence: 99%
“…Rajak et al [ 32 ] found that nearly a quarter (24.7%) of those having received lamellar tarsal rotation suffered recurrence. Researchers note though that recurrence rates tend to be higher in those nurse-surgeons who performed the procedure only infrequently, an argument for frequent in-service training and practice [ 33 ].…”
Section: Tertiary Prevention Activitiesmentioning
confidence: 99%
“…13 The fact that sick children presenting to hospitals are generally accompanied by a caregiver provides an innovative, scalable framework for implementation of our findings. While task shifting has been widely described among skilled and semi-skilled health care workers, [14][15][16][17][18] further research is needed on the effectiveness and safety of this approach when applied to caregivers and other laypersons.…”
Section: Discussionmentioning
confidence: 99%
“…Task-shifting, a process of delegation where clinical tasks are shifted to less specialized health workers where appropriate, has been used successfully to improve access to HIV services in low income countries [ 3 ]. Adaptions of this strategy for cataract and trichiasis surgery have had limited impact [ 4 , 5 ]. Training primary healthcare workers to deliver primary eye care (PEC) offers a pragmatic approach to address the eye health workforce shortages through improving access and reducing demand for specialist care.…”
Section: Introductionmentioning
confidence: 99%